The problem of effective and safe treatment of acute respiratory infections in children - T.A. Kruchko; O.Ya. Tkachenko; V.P. Harshman; O.P. Ivanenko (Zaslavsky O.Yu., 2017)
As the etiological structure of acute respiratory viral infections (ARVI) is polymorphic, the presence of clinical manifestations very rarely allows to establish a connection with a particular pathogen and to prescribe the proper causal treatment. The purpose of this clinical study was to examine the effectiveness of Imupret® in the treatment of acute respiratory viral infections in children (n = 35) of pre-school and primary school age. All patients received symptomatic treatment according to the current order of the Ministry of Healthcare of Ukraine. The main group (n = 18) received additional immunomodulatory herbal drug Imupret®. In order to monitor the course of ARVI, parents filled in the diaries, which included an assessment of nine core symptoms. In children of the main group, we noted improving the clinical index from the 3rd day compared to the controls. Significant differences were observed between patients, when assessing the nature of cough, namely its earlier moistening effect and increased productivity in children, who received additional Imupret® with complete regression in both groups up to the 12th day. The average duration of ARVI in the study group was 6.2 days compared with 8.9 days in the control group. Analyzing the incidence of respiratory diseases, we found out that within three months in the children, who were treated with Imupret®, recurrent episodes were observed in only 28 % of cases, whereas viral infection in children in the control group was registered in almost half of the cases. Imupret® is safe and effective drug of natural origin with a proven mechanism of action for the treatment and prevention of ARVI in children.